La salud como derecho en el postconflicto colombiano (2018)
Objective To explore the elements that should be considered in post-conflict zones to guarantee the right to health of populations immersed or living in areas near the concentrations of former combatants. Materials and Methods A retrospective study was carried out by searching databases, obtaining 26 relevant articles. Results The literature review made evident that not only the legal or normative framework is important, but also the needs and interests of the people of the community, of both the civilian population and the victims of war. The right to health in these areas also involves the exercise of power, of dialogue of knowledge, forgiveness, non-re-petition and respect. In addition, health promotion and disease prevention services, treatment and rehabilitation based on the primary care strategy should be offered, that is, they should be adapted to the cultural realities, the environments and the interests of the communities. Conclusions The challenge lies in the way how these goals can be achieved within a context of a weak health system, in financial, administrative and technical terms. Basic multidimensional elements in the field of primary health care are proposed to face this challenge for the Colombian public health. © 2018, Universidad Nacional de Colombia. All rights reserved.